Arabic Language Education KKN Programs to improve Al-Quran Memorization at Tahfidz Schools - Ahmad Zaky; Ridha Annisa; Suchi Nurul Khofifah; Maya Sari; Nur Asia Siregar; Nur Khalisah Nasution; Maytri Wulandari (As-sunnah: Jurnal Pengabdian Masyarakat, 2023)
Real Work Lecture (KKN) is one of the lecture activities held by STAI As-Sunnah, with the community as the main object in its implementation. This year's KKN was held in the month of Ramadan 2022. The Implementation Team was formed into several specific groups and would carry out their respective duties at the agreed place. KKN for the group that chose Ma'had Tahfizh Al-Qur'an Lil Al-aytam wa Adh-Dhu'afa' Kitabina as the object went well as planned previously. The Implementation Team held many activities aimed at optimizing the development of female students' Arabic with Arabic learning models and strategies oriented towards the activeness of the Implementation Team to make learning effective and efficient in achieving the objectives of Arabic Learning itself, both from Arabic Proficiency or Language Elements Arabic itself, so that the program applied to Ma'had Tahfizh Al-Qur'an Lil Al-aytam wa Adh-Dhu'afa' Kitabina is able to increase memorization and understanding of the Al-Qur’an as the purpose and institution of this school, the programs held there are in the form of refining tahsin, learning Arabic, awarding mufrodat, implementing ta'lim, studies, and competitions in Arabic.